Analisis Penerapan PSAK 109 Pada Badan Amil Zakat Serta Pengelolaan Dana Zakat (Studi Kasus BAZNAS Kab. Malang) - Ramadhiyani, Laila Qaddariah; Askandar, Noor Shodiq; Anwar, Siti Aminah (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research is based on information about the application of PSAK 109 which is designed for financial statements for zakat, infaq and alms, where the case study of this research is at BAZNAS, Malang District, located in Kepanjen. This type of research uses qualitative research with an analytical descriptive method approach, using primary and secondary data, this data collection technique uses previous literature, interviews and documentation. The simplification of this research revealed that BAZNAS Malang Regency has used PSAK 109, it's just that in the distribution of funds it does not specifically mention zakat recipients and the distribution of zakat funds is distributed through the program.Keywords : BAZNAS Kab. Malang, PSAK 109, zakat